2022
DOI: 10.3389/fmicb.2022.802577
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Species-Specific Virome in Culicoides of Thrace

Abstract: Biting midges (Culicoides) are vectors of arboviruses of both veterinary and medical importance. The surge of emerging and reemerging vector-borne diseases and their expansion in geographical areas affected by climate change has increased the importance of understanding their capacity to contribute to novel and emerging infectious diseases. The study of Culicoides virome is the first step in the assessment of this potential. In this study, we analyzed the RNA virome of 10 Culicoides species within the geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 97 publications
(141 reference statements)
1
3
0
Order By: Relevance
“…Viruses of the Rhabdoviridae, Polycipiviridae, Phasmaviridae, Phenuiviridae, and other virus families were identified in this study, as in other studies, but in markedly different proportions ( 32 ). In this study, Polycipiviridae viruses (e.g., Hubei picorna-like virus 82, a ssRNA + insect-related virus found in spiders) were very abundant in Culicoides viromes, which has not been reported previously.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Viruses of the Rhabdoviridae, Polycipiviridae, Phasmaviridae, Phenuiviridae, and other virus families were identified in this study, as in other studies, but in markedly different proportions ( 32 ). In this study, Polycipiviridae viruses (e.g., Hubei picorna-like virus 82, a ssRNA + insect-related virus found in spiders) were very abundant in Culicoides viromes, which has not been reported previously.…”
Section: Discussionsupporting
confidence: 81%
“…Meta-viromic approaches have enabled the characterization of viromes carried by Culicoides in some regions and promoted the discovery of new viruses. Analysis of the RNA viromes of 10 Culicoides species in Thrace, southeastern Europe, led to the identification of novel RNA viruses with genomic signatures and revealed that each Culicoides species carried a specific virus set ( 32 ). The viromes of Culicoides impunctatus populations in Scotland ( 33 ), Culicoides imicola in Senegal ( 34 ), Culicoides arakawae in Japan ( 35 ), and mixed Culicoides populations ( 6 , 36 ) have been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, additional efforts to validate the identity of the generated mitochondrial genomes are needed [ 9 ]. The mitogenome of the host Bos taurus was recovered from C. biguttatus DNA reads, confirming the potential of metagenomics for studying vectors and their hosts simultaneously, as well as potentially vectored pathogens [ 35 37 ]. Notably, all C. biguttatus specimens used for mitogenome reconstruction were sampled in a dairy barn.…”
Section: Discussionmentioning
confidence: 89%
“…Studies on the microbiota of Culicoides biting midges are scarce, mainly restricted to the bacterial midgut fauna, and differentiation, in the best case, to the genus level [183][184][185][186]. A few studies exist on the virome of Culicoides species [187][188][189][190]. Both groups of studies do not consider biotic interactions or correlate the midgut fauna with pathogen infection of the insect host, although an impact of bacteria and viruses must be considered likely based on studies with mosquitoes [191].…”
Section: Culicoides Microbiota and Its Interaction With Culicoid-born...mentioning
confidence: 99%